Autophagy-Related Gene ATG7 Polymorphism Could Potentially Serve as a Biomarker of the Progression of Atrophic Gastritis - Yamaguchi, Naoyuki; Sakaguchi, Takuki; Taira, Miki; Fukuda, Daisuke; Ohnita, Ken; Hirayama, Tatsuro; Yashima, Kazuo; Isomoto, Hajime; Tsukamoto, Kazuhiro (Journal of Clinical Medicine, 2024)
Cytotoxin-associated gene A (CagA) is an oncoprotein that H. pylori injects into the host’s gastric epithelial cells and that induces proinflammatory cytokines, such as interleukin (IL)-18 and IL-1β. As a result, it leads to atrophic gastritis (AG), a precancerous lesion of gastric cancer. On the other hand, host cells degrade CagA using autophagy systems. However, few studies exist about the single nucleotide polymorphisms (SNPs) in MAP1LC3A, MAP1LC3B, ATG4A, ATG4B, ATG4C, ATG7, and ATG13, which belong to the autophagy-related genes concerning AG. This study aimed to detect biomarkers associated with AG. Herein, H. pylori-positive subjects (n = 200) were divided into the AG (n = 94) and non-AG (n = 106) groups. Thirty tag SNPs were selected from the above seven candidate genes. The SNP frequency between the two groups was analyzed. The frequency of the C/T or T/T genotype at rs4683787 of ATG7 was significantly lower in the AG group than in the non-AG group (p = 0.034, odds ratio = 0.535). Based on multivariate analysis, the C/C genotype of rs4684787 and age were independently associated with gastric mucosal atrophy. This finding helps stratify the patients needing timely endoscopic screening or early eradication of H. pylori.